Wacana Iklan Komersial Busana Wanita dalam Media Sosial Instagram - Elita Ulfiana (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
This study examines the discourse of Commercial Ads of Women's Clothing in Social Media Instagram that focuses on the act of illocution and persuasion techniques in an advertisement of women's clothing products. The discussion aims to describe the structure of the Discourse of Commercial Ads of Women's Clothing in Social Media Instagram and explains the act of speech and persuasion techniques of Commercial Ads of Women Fashion in Instagram Social Media. From the structure analysis seen the act of speech used by producer in making advertisement. The type of speech acts widely used by producers is the act of speech illocution. The actuarial speeches contained in the Commercial Ads of Fashion Lingerie in Instagram Social Media are acutive, directive, commissive, and expressive illustrations, while persuasive techniques used in Women's Commercial Literacy Commercial Ads in Instagram Media include (1) techniques persuasive through gift giving, (2) persuasive techniques through charity, (3) persuasive techniques through challenges.